Yahoo Web Search

  1. Sort by

  1. You have that: dv/dt = k*v^2 and you should already be able to tell that k is going to be a... that when v = 5 m/s, dv/dt = -1 m/s^2, so: -1 m/s^2 = k*(5 m/s)^2 k = -1/(25 m) The original differential equation is separable: v^(-2) dv...

    1 Answers · Science & Mathematics · 20/10/2009

  2. ... about the Arrhenius equation as the model, correct? k = A0 * Exp( Ea / RT ) where k...) * (1/T) + ln A0 If we let y = ln k b = ln A0 m = Ea / R x = 1/T...

    1 Answers · Science & Mathematics · 05/10/2009

  3. The period (T1) of a mass (m1) on a spring(k) is: T1 = 2 pi sqrt (m1/k) Solve for...proportional to the square of the period (instead of plugging in k and canceling). Anyway, they give you the...

    1 Answers · Science & Mathematics · 26/02/2010

  4. Use conservation of energy (K + U)1 = (K + U)2 K1 = 0 and U1 = 0 (Set...

    1 Answers · Science & Mathematics · 05/03/2011

  5. ... know that the drop gains mass according to: dM/dt = k*S = k*4*pi*r^2 Substitute the expression for the mass as a function...

    2 Answers · Science & Mathematics · 27/06/2006

  6. 1) k = Force/ displcement = NEwton / m = kg m /(s^2 m) = kg /s^2 so dimensional formula [ M^1 T^-2] 2) k= Force/ Velocity ^n = kg m s^n __________ (s^2)(m^n) = kg m...

    2 Answers · Science & Mathematics · 11/01/2011

  7. K.E = 1/2mv^2 wher, m is mass = 1 kg v is velocity = 6m/s K.E = 1/2(1)(6)^2 K.E = 1/2(36) K.E = 18 joules

    1 Answers · Science & Mathematics · 22/10/2012

  8. Given: f(E)=e^(-(E/(k∗T))−(b/√E)) = {e^(-(E/(k∗T)))}{e^−(b/√E...)v(E) + u(E)v'(E) d{f(E)}/dE = {-(1/(k∗T)e^(-(E/(k∗T)))}{e^−(b/√E)} + {e^(-(E/(k...

    1 Answers · Science & Mathematics · 12/02/2013

  9. "The Isotope potassium K (atomic number = 40 mass number = 19)"... new element (Z=18) is argon. So K-40 has turned in Ar-40. We...

    2 Answers · Science & Mathematics · 18/12/2011

  10. for spring restorative force F = - k x m dv / dt = - k x dv = - k/m x dt dv = - k/m x {dx/v} v dv = - k/m dx...0 (spring retreats after reaching amplitude ------------------------- 0 = - k/m (a^2) + c1 >>> c1 put back (v^2) = - k/m (x^2) + k/m (a^2) v^2 = k...

    2 Answers · Science & Mathematics · 27/04/2007

  1. Ad
    related to K
  1. Try asking your question on Yahoo Answers